A solution to improve heat dissipation for closed circuit board chassis - Lê Thạc, Tài; Trần Hồng Quân (Journal of Military Science and Technology, 2022)
This paper presents the results of research on a solution to increase the heat dissipation for the enclosure containing the closed circuit board using a blower to circulate the air inside. Building models and methods to solve heat transfer problems. On that basis, investigating the influence of air flow velocity on the temperature difference between the inside and the outside environment and the chip surface temperature. The article also proposes to choose the right type of blower for a heat dissipation plan with a specific heat source capacity and conduct verification tests. The research results of the article can be applied when designing a heatsink housing containing a closed circuit board.